Mental models on Philippine English in online spaces : challenges and opportunities - Paz, Rafael Michael (Penerbit Universiti Kebangsaan Malaysia, 2022)
For the majority of the elite and educated Filipinos, there is no doubt that Philippine English finds its home as an acceptable variety of English. However, the narrative changes once focus is decentralized and democratized to include other speakers of English in the country who do not belong to this exclusive social category. Using online comments to an online news article and to an online quote card about Philippine English, this study investigated the acceptability of Philippine English among the users of a social media space. Comments were gathered and then analyzed using the arrangement of propositions from the prompt (the online article and quote card) to the determination and thematic categorization of mental models deployed by commenters to interpret received information. The analysis revealed that within the online platform where various realizations of English are welcome, Philippine English remains contested. This paper encourages the inclusive education and information dissemination that focus on Philippine English across sociolectal groups to strengthen the knowledge, acceptance, and educational implementation of the principles and concepts related to Philippine English.